Relationship between eosinopenia and neutrophil-lymphocyte ratio with sepsis-related mortality in the intensive care unit - Parviz Amri; Armin Nejadnaderi; Hemmat Gholinia; Fatemeh Heidarnia; Masomeh Bayani (Caspian Journal of Internal Medicine)
Background: Early diagnosis of sepsis can lead to rapid initiation of treatment and reduced mortality. The aim of this study was to investigate the relationship between eosinopenia and neutrophil-lymphocyte ratio (NLR) with sepsis-related mortality in the intensive care unit. Results: Out of 100 patients studied, 59 patients survived and 41 patients died and the mean age of the patients was 63.27±16.13 years. Out of 40 patients with eosinopenia, 19(46.3%) died and out of 60 patients with normal eosinophil, 22(53.7%) died (P=0.28). The NLR on the first day in died patients was significantly higher than in the surviving patients (P=0.009). The increase in SOFA Score (p<0.001 and OR=1.49) and the increase in NLR (P=0.02 and OR=3.38) has a direct relationship with the mortality rate. Conclusion: The results of the present study in sepsis patients showed that patients who had a higher neutrophil-to-lymphocyte ratio had higher mortality and there was no relationship between eosinopenia and mortality rate.